MONITORING EARTH DEFORMATION AND SUBSIDENCE USING GEOLOGY - T. T. Salaydinov; O. O. Mamatkulov (European Science Publishing, 2024)
Earth deformation and subsidence are natural processes that can have significant impacts on infrastructure, the environment, and human settlements. In recent years, advances in geology have enabled scientists to monitor these processes more effectively. This article discusses the importance of monitoring earth deformation and subsidence using geological techniques, including remote sensing, GPS technology, and geological surveys.
Keywords: Earth deformation, subsidence, geology, monitoring techniques, remote sensing, GPS technology.